Social management in the system of physical education and sports of employees of internal affairs of Ukraine - Babenko V.G (Kharkov National Pedagogical University, 2013)
The main forms, principles and methods of the physical training's management of the Internal Affairs Agencies's staff are considered. Reveals its consistency and conceptual approach to the mechanism of targeted and effective operation of the system under different conditions of the employees police. Determined that the system of physical training and sports of bodies and organs of internal affairs of Ukraine, except for departmental purposes, partly related to the overall social and cultural life of modern society, and the management of this system is social in nature and depends on the level of socialization of its top performers and other regional representatives. It is set that optimization of correction foresees subsequent purposeful realization of the planned complex of measures which answer certain terms and real possibilities of operating control the system.